Antimicrobial activity of ceftazidime-avibactam and comparators against levofloxacin-resistant Escherichia coli collected from four geographic regions, 2012-2018 - Gregory G. Stone; Meredith A. Hackel (BMC, 2022)
Abstract Background Increases in resistance to fluoroquinolones have been correlated with the use of levofloxacin in the treatment of infections caused by Escherichia coli. The analysis presents the in vitro activity of ceftazidime-avibactam and comparator agents against 10,840 levofloxacin-resistant E. coli isolates collected from four geographic regions (Africa/Middle East, Europe, Asia/South Pacific, Latin America) between 2012 and 2018. Methods Non-duplicate clinical isolates of E. coli were collected from participating centres and shipped to IHMA, Inc., (Schaumburg, IL, USA). Susceptibility testing was performed with frozen broth microdilution panels manufactured by IHMA, according to CLSI guidelines. Levofloxacin-resistance was defined at a minimum inhibitory concentration of ≥ 2 mg/L. Isolates collected between 2012 and 2015 were tested for extended-spectrum β-lactamase (ESBL) activity by determining susceptibility to cefotaxime, cefotaxime-clavulanate, ceftazidime, and ceftazidime-clavulanate as recommended by CLSI guidelines. Isolates collected between 2016 and 2018 were identified as ESBL-positive by genotype using multiplex polymerase chain reaction assays. Results A total of 74.8% of levofloxacin-resistant E. coli isolates in the analysis were from three culture sources: urinary tract infections (N = 3229; 29.8%), skin and skin structure infections (N = 2564; 23.7%) and intra-abdominal infections (N = 2313; 21.3%). Susceptibility rates to ceftazidime-avibactam were consistently high in all regions against both ESBL-positive (97.0% in Asia/South Pacific to 99.7% in Africa/Middle East and Latin America) and ESBL-negative isolates (99.4% in Asia/South Pacific to 100% in Latin America). Susceptibility was also high in each region among ESBL-positive and ESBL-negative isolates to colistin (≥ 98.5%), imipenem (≥ 96.5%), meropenem (≥ 96.5%) and tigecycline (≥ 94.1%). Conclusions Antimicrobial susceptibility to ceftazidime-avibactam among levofloxacin-resistant E. coli isolates, including ESBL-positive isolates, collected from four geographical regions between 2012 and 2018 was consistently high. Susceptibility to the comparator agents colistin, tigecycline, imipenem and meropenem was also high.